Geostrategies of the european neighbourhood policy - Christopher S. Browning; Pertti Joenniemi (Danish Institute for International Studies (DIIS), 2007)
The debate about the European Neighbourhood Policy (ENP) has, in essence, been about borders and bordering. Such departures often contribute to rather fixed geopolitical visions of what the EU is about and how it aims at running and organising the broader European space. In contrast, this paper aims at retaining space for viewing the ENP as a developmental and somewhat fluid process. A conceptual framework, based on the outlining of three geopolitical models and a series of different geostrategies employed by the EU in regard to its borders, is hence utilized in order to tell a more dynamic story regarding the developing nature of the ENP and the EU's evolving nature more generally. The complexity traced informs that various geostrategies may be held at the same time at the external border. Moreover, the dominance of one geostrategy may be replaced by another or a different combination of them with regard to the same neighbourhood. It is, more generally, argued that if anything it is precisely this dynamism that should be championed as a valuable resource and as such avoiding the tendency to close off options through the reification of particular visions of the nature of the EU and ist borders.
Keywords: 330; Geopolitik; EU-Staaten